2004
DOI: 10.1128/aem.70.3.1836-1842.2004
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Pathogen Signaling in Multitrophic Plant-Microbe Interactions Involved in Disease Protection

Abstract: Multitrophic interactions mediate the ability of fungal pathogens to cause plant disease and the ability of bacterial antagonists to suppress disease. Antibiotic production by antagonists, which contributes to disease suppression, is known to be modulated by abiotic and host plant environmental conditions. Here, we demonstrate that a pathogen metabolite functions as a negative signal for bacterial antibiotic biosynthesis, which can determine the relative importance of biological control mechanisms available to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 67 publications
2
52
0
2
Order By: Relevance
“…Therefore, more phlD genotypes and their respective DAPG-deficient mutants need to be tested to more conclusively assess the contribution of the antibiotic DAPG in the natural soil suppressiveness to Fusarium wilt disease. Furthermore, DAPG biosynthesis may also have been repressed by specific environmental conditions (Duffy and Défago, 1999) or by fusaric acid ( Figure 5; Notz et al, 2002;Duffy et al, 2004), a phytotoxin produced by pathogenic F. oxysporum and non-pathogenic F. oxysporum strain Fo47 (Schouten et al, 2004). However, given that also phenazine production can be repressed by fusaric acid (Van Rij et al, 2004, it seems unlikely that this phytotoxin played a major role in the multitrophic interactions occurring in the biocontrol assays.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more phlD genotypes and their respective DAPG-deficient mutants need to be tested to more conclusively assess the contribution of the antibiotic DAPG in the natural soil suppressiveness to Fusarium wilt disease. Furthermore, DAPG biosynthesis may also have been repressed by specific environmental conditions (Duffy and Défago, 1999) or by fusaric acid ( Figure 5; Notz et al, 2002;Duffy et al, 2004), a phytotoxin produced by pathogenic F. oxysporum and non-pathogenic F. oxysporum strain Fo47 (Schouten et al, 2004). However, given that also phenazine production can be repressed by fusaric acid (Van Rij et al, 2004, it seems unlikely that this phytotoxin played a major role in the multitrophic interactions occurring in the biocontrol assays.…”
Section: Discussionmentioning
confidence: 99%
“…Fusarium spp. are common soil fungi, which can have important roles not only as plant pathogens, but also as saprotrophic competitors of other pathogenic fungi (Duffy et al, 2004;Yergeau et al, 2005). In this study, the density of Fusarium spp., as judged by quantitative real-time PCR targeting the 18S-rRNA gene, was significantly reduced in the rhizosphere of the mycorrhizal plant (F. rubra) exposed to elevated atmospheric CO 2 concentration.…”
Section: Effects Of Elevated Co 2 On Fungal Communitiesmentioning
confidence: 99%
“…Fusaric acid produced by Fusarium was shown to be the fungal metabolite that specifically repressed DAPG biosynthesis (Duffy and Défago 1997;Notz et al 2002): blocking fusaric acid production in Fusarium by addition of zinc relieved repression of the phlA gene and improved the activity of strain CHA0. Subsequent studies showed that among a collection of genotypically different DAPG-producing Pseudomonas strains, several were relatively insensitive to fusaric acid-mediated repression of DAPG biosynthesis (Duffy et al 2004).…”
Section: Interference With the Biosynthesis Of Antimicrobial Compoundmentioning
confidence: 99%